Perbandingan Metode SAW dan CPI dalam Sistem Pendukung Keputusan untuk Menilai Kinerja Guru - Andi Loa; Benny Daniawan; Tugiman Tugiman; Amat Basri (Komunitas Dosen Indonesia, 2020)
At educational institutions like Junior High School, Human Resources especially teachers determines the quality of the school. To determine Junior High School have good quality teachers, then the best teacher selection is needed to spur the teacher's performance. However, the best teacher selection at Santa Maria 2 Junior High School which in Tangerang still doing direct observation and no method implements the calculation. To overcome those problems, then Decision Support System is needed to do a calculation and rating the teachers at ease and accurate. The proposed Decision Support System is using Simple Additive Weighting and Composite Performance Index methods, where’s the calculation is obtained from each alternatives score and value weight from each criterion. The criteria in best teacher selection are reviewed from the absence aspect, professionalism, solidarity corps, personality, involving in activities from inside or outside school events. The final result from this calculation formed to ranking. The execution time of the SAW method has a faster average time of 0.489005 than the CPI method with an average time of 0.62258 seconds. On Relative Standard Deviation Testing CPI percentage greater than SAW with 3.90% and CPI 6.48%.